Reduction of senescence‐associated beta‐galactosidase activity by vitamin E in human fibroblasts depends on subjects’ age and cell passage number - Ricciarelli, Roberta; Azzi, Angelo; Zingg, Jean‐Marc (BioFactors (Oxford), 2020)
Cell senescence is due to the permanent cell cycle arrest that occurs as a result of the inherent limited replicative capacity toward the Hayflick limit (replicative senescence), or in response to various stressors (stress‐induced premature senescence, SIPS). With the acquisition of the senescence‐associated secretory phenotype (SASP), cells release several molecules (cytokines, proteases, lipids), and express the senescence‐associated beta‐galactosidase (SA‐β‐Gal). Here we tested whether vitamin E affects SA‐β‐Gal in an in vitro model of cell ageing. Skin fibroblasts from human subjects of different age (1, 13, 29, 59, and 88 years old) were cultured until they reached replicative senescence. At different passages (Passages 2, 9, 13, and 16), these cells were treated with vitamin E for 24 hr. Vitamin E reduced SA‐β‐Gal in all cells at passage 16, but at earlier passage numbers it reduced SA‐β‐Gal only in cells isolated from the oldest subjects. Therefore, short time treatment with vitamin E decreases SA‐β‐Gal in cells both from young and old subjects when reaching replicative senescence; but in cells isolated from older subjects, a decrease in SA‐β‐Gal by vitamin E occurs also at earlier passage numbers. The possible role of downregulation of CD36 by vitamin E, a scavenger receptor essential for initiation of senescence and SASP, is discussed.